(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article talks about the methodology of foreign language teaching, the history of its development as a science, the types of modern methods used in the methodology of foreign language teaching and their use. In addition, the training of specialists who can perfectly learn foreign languages and can speak fluently in the foreign language they are learning, the training of personnel who meet the requirements of entering into the culture of the peoples of the world by learning foreign languages is the goal of the educational reform in our country and one of the tasks.